Environmentally benign synthesis of beta-hydroxy sulfides using cyclic carbonates catalyzed by large-pore zeolites - Upare, Pravin P.; Kinage, Anil K.; Shingote, Savita K.; Gupte, Sunil P. (Green Chemistry Letters and Reviews, 2012)
An efficient one-pot synthesis of beta-hydroxy sulfides from thiophenol and cyclic carbonates catalyzed by large-pore zeolites has been reported. Reaction of thiophenol with ethylene carbonate in the presence of the Na-X zeolite catalyst gave the highest yield of 2-(phenylthio)ethanol (100%), while reaction with propylene carbonate a highest yield of regioselective product 1-(phenylthio)propan-2-ol was obtained (97%). Enantiomerically pure 1,2-propylene carbonate gave highly regioselective and stereospecific phenylthiopropanol, demonstrating that original chirality of propylene carbonate is retained. A plausible mechanism has been proposed for zeolite-catalyzed transformation involving a chemoselective nucleophilic attack of thiophenoloxide ion onto the less-substituted carbon of cyclic carbonate. The Na-X zeolite catalyst is recyclable and provides advantages of green chemistry approach to the synthesis of beta-hydroxy sulfides without the use of any solvent.
Keywords: beta-hydroxy sulfide; ethylene carbonate; propylene carbonate; thiophenol; zeolite

Methanesulfonic acid-catalyzed friedel-crafts alkylation: towards sustainable synthesis of arylalkanes from donor-acceptor cyclopropane ketones - Goswami, Lakshmi; Paul, Sayantan; Mamale, Ajay G.; Gonnade, Rajesh G.; Bhattacharya, Asish K. (Asian Journal of Organic Chemistry, 2024)
We present herein Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane ketones. The presence of the 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules inspired us to pursue the direct synthesis of these structural frameworks. Utilizing methanesulfonic acid (MeSO3H) as a catalyst, we achieved a more environmentally friendly and high-yielding synthesis, owing to its cost-effectiveness, biodegradability, transition-metal and additives free conditions. Furthermore, we have successfully extended our developed methodology to thiophenols, resulting in the production of sulfur-based butan-1-one derivatives in good yields. The presence of 1,4-diphenyl butan-1-one and 1,3-diphenyl propane-1-one motifs in various naturally occurring biologically significant molecules prompted us to develop a Br & oslash;nsted acid-catalyzed Friedel-Crafts alkylation of phenols with Donor-Acceptor cyclopropane. image
Keywords: donor-acceptor cyclopropane; Friedel-Crafts alkylation; methanesulfonic acid; Phenols; thiophenol